Who is Satan? : according to the scriptures - Kelly, Joseph F. (Joseph Francis), 1945- (Collegeville, Minnesota : Liturgical Press, 2013)
How does the Bible's teaching on the devil square with psychology and other modern scientific disciplines that seem to have driven Satan into the realm of myth? Why does 666 signify the devil? Is Satan the Antichrist or does that term refer to a human? Popular media has combined a number of diverse traditions, distorting Christian teaching and tradition about Satan and also occasionally distorting common sense. Kelly introduces the reader to what the Bible actually says about Satan and other evil biblical figures.
The problem of Satan -- The problem of evil in the Old Testament -- Jewish apocryphal literature -- The devil in the New Testament: the Pauline Epistles -- The devil in the Gospels: Mark and Matthew -- The devil in the Gospels: Luke, John, and Acts of the Apostles -- The devil in later Epistles -- The Book of Revelation -- The early Christian creation of Satan -- Satan today.
Includes bibliographical references (pages 153-155).
Print version record.
Keywords: Devil -- Biblical teaching; Devil -- Biblical teaching; RELIGION / Christian Theology / Angelology & Demonology; Electronic books; Electronic books